Comparative Analysis of the Full-Length Genome Sequence of a Clinical Isolate of Human Parainfluenza Virus 4B. (19th July 2012) - Lednicky, John A.; Waltzek, Thomas B.; Halpern, Micah D.; Hamilton, Sara B.
Abstract : We are engaged in airborne transmission and epidemiology studies of respiratory pathogens, with particular interest in human parainfluenza virus type 4 (hPIV-4) and other lesser studied viruses. In this paper, hPIV-4 was detected in primary rhesus monkey kidney (PRMK) cells that had been inoculated with nasopharyngeal swab material obtained from a child with a mild upper respiratory tract illness. Attempts to isolate the virus in pure culture were hampered by the presence of a fast-growing simian spumavirus that was a contaminant of the PRMK cells. Total RNA was extracted from the PRMK cell culture, and PCR followed by sequencing of a subgenomic section of the fusion protein gene suggested the hPIV-4 was subtype 4B. At the time of this work, two complete but dissimilar hPIV-4B genomes had been deposited by others in GenBank. To gain better insights on hPIV-4B, and to test methods that we are developing for viral forensics, the entire genomic sequence of our virus was determined from archived RNA. The hPIV-4B genomic sequence that we determined conforms to the paramyxovirus "rule of six." Here, we compare and contrast the genetic features of the three completely sequenced hPIV-4B genomes currently present in GenBank.